2017
DOI: 10.4103/ijd.ijd_148_17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, histopathological characteristics and immunohistochemical findings in lichen planus pigmentosus

Abstract: Background:Lichen planus pigmentosus (LPP), a rare variant of lichen planus, is reported in various ethnic groups, more often from the Indian subcontinent and the Middle East.Aims:Although the condition is encountered quite often by dermatologists of this region, the data on the clinical, pathological, and immunohistochemical (IHC) aspects of LPP are limited. This prospective study is aimed towards filling this lacuna.Materials and Methods:Data were collected from thirty clinically diagnosed cases of LPP who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 24 publications
3
35
0
1
Order By: Relevance
“…[ 9 ] Studies had examined TNF-α, IL-2, IFN-γ, IL-6, IL-1β, and lymphotoxin levels in serum of patients with oral lichen planus, and they found that only TNF-α and IL-6 levels were higher in patients with oral lichen planus compared to that of the control group. [ 10 11 ] Recent studies have shown that TNF-α production was high in mononuclear cells and keratinocytes when the patients with nonlesional or normal oral mucosa and oral lichen planus were compared to each other. [ 12 ] In a study conducted by Kaur and Jacobs in Korea in 2016, serum and saliva TNF-α concentrations in patients with oral lichen planus were higher than those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Studies had examined TNF-α, IL-2, IFN-γ, IL-6, IL-1β, and lymphotoxin levels in serum of patients with oral lichen planus, and they found that only TNF-α and IL-6 levels were higher in patients with oral lichen planus compared to that of the control group. [ 10 11 ] Recent studies have shown that TNF-α production was high in mononuclear cells and keratinocytes when the patients with nonlesional or normal oral mucosa and oral lichen planus were compared to each other. [ 12 ] In a study conducted by Kaur and Jacobs in Korea in 2016, serum and saliva TNF-α concentrations in patients with oral lichen planus were higher than those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory phase of the skin lesions that affected our patient in case 4, although uncommon, should remind us that the presence of inflammatory cells in the early phases of LPPig supports the indication for early treatment to avoid chronic persistent pigmentation [14]. Early intervention with systemic steroids or other agents such as methotrexate can probably help prevent hyperpigmentation, as in our case.…”
Section: Discussionsupporting
confidence: 51%
“…It is known that the same autoimmune mechanism where cytotoxic T-cell response is generated and genetic predisposition and autoimmunity of ankylosing spondylitis and LPP are also responsible for the etiopathogenesis in ankylosing spondylitis, which is one of the sero-negative spondyloarthropathies, genetically associated with HLA-B27 11 . Bhat et al 12 found that 26% of 30 clinically diagnosed LPP patients reported associations such as hypertension, diabetes mellitus, hypothyroidism and epilepsy. Karn et al 13 found that thyroid peroxidase autoantibodies were significantly higher in 54 patients with LPP compared to the control group.…”
Section: Discussionmentioning
confidence: 99%